Degradation of polycaprolactone/starch blends and composites with sisal fibre - Di Franco, C.R. (2004)
The susceptibility of polycaprolactone/starch (PCL/S) and sisal fibre-reinforced polycaprolactone/starch blends (SF-PCL/S) to different degrading environments was evaluated. The composites and the unfilled matrix showed hydrolytic stability at pH 7.2 at two different temperatures (25 °C and 40 °C). Fibres were stable under hydrolytic conditions and seemed to favour the entrance of water and then, the swelling and the hydrolysis of the starch (the most bio-available component). At higher fibre content, the composites become more hydrolytically stable probably due to the presence of a fibre–fibre physical network. Microbial attack in biotic aqueous medium was evidenced by the presence of a biofilm, especially on the fibre surface. In soil burial, PCL/S and 15%SF–PCL/S were degraded to about 50% of the initial mass. The weight loss pattern showed by the composite was associated with the presence of strong fibre–fibre and fibre–matrix interactions, which are absent in the neat matrix.